Some species of Oedogoniales (Chlorophyceae) from small astatic water bodies in the post-agricultural landscape (Masurian Landscape Park, NE Poland) - Szymańska, Hanna; Krzyk, Agnieszka; Mętrak, Monika (Phytotaxa, 2015)
This paper presents a report on epiphytic green algae belonging to Oedogoniales from astatic and moderately eutrophic small ponds in the Masurian Landscape Park, NE Poland. During this investigation, 26 species of Oedogoniales have been identified and described including one variety (O. oblongum var. longisporum) new to science and two species (O. fremyi and O. irregulare) new to the algal flora of Poland.